2020
DOI: 10.4081/jphr.2020.1861
|View full text |Cite
|
Sign up to set email alerts
|

Are Young Adults with Long-Standing Illness Or Disability at Increased Risk of Loneliness? Evidence from the Uk Longitudinal Household Study

Abstract: Background: Recent evidence has shown that young adults experience significant levels of loneliness, and those with long-standing illness or disability (LSID) may be particularly vulnerable. This study investigated whether young adults with LSID were more likely to experience loneliness than their ‘healthy’ peers, after accounting for key socio-contextual and health-related factors associated with loneliness.Design and Methods:  The sample consists of 4510 16-24-year-old individuals from W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Meanwhile, young adults with a pre-existing mental health problem or one or more long-standing physical health conditions reported higher loneliness levels during this unusual period, coinciding with previous research ( McGlone and Long, 2020 ; O'Connor et al., 2020 ). The current findings reaffirm the heightened risks brought by these long-term conditions, calling attention to tailoring interventions for vulnerable young adults.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Meanwhile, young adults with a pre-existing mental health problem or one or more long-standing physical health conditions reported higher loneliness levels during this unusual period, coinciding with previous research ( McGlone and Long, 2020 ; O'Connor et al., 2020 ). The current findings reaffirm the heightened risks brought by these long-term conditions, calling attention to tailoring interventions for vulnerable young adults.…”
Section: Discussionsupporting
confidence: 88%
“…COVID-focused studies with UK samples have shown that females and those with low income or who are unemployed were more likely to experience loneliness, whereas those living with a romantic partner were less likely to feel lonely ( Bu et al., 2020 ; Li & Wang, 2020 ; O'Connor et al., 2020 ). Other important covariates related to increased loneliness during the pandemic include physical and mental health problems ( McGlone & Long, 2020 ; O'Connor et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…27 Responses to the three items were summed, creating a variable ranging from 0 to 6. In line with previous use of this scale, [28][29][30] we considered loneliness as a continuous outcome.…”
Section: Lonelinessmentioning
confidence: 99%
“…For example, loneliness is more prevalent among YAs than older adults, 12,13 and YAs with longstanding illness, such as cancer, have higher incidence and severity of loneliness than healthy peers. 14 Social connectedness is another determinant of health that is theorized to mechanistically underlie the health-promoting effects of social relationships. 15 It is linked to longer life expectancy, better mental health, better cognitive functioning, and enhanced neuroendocrine and immune regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although most research on social isolation has focused on older adults, emerging evidence underscores its relevance for YAs. For example, loneliness is more prevalent among YAs than older adults, 12,13 and YAs with long‐standing illness, such as cancer, have higher incidence and severity of loneliness than healthy peers 14 …”
mentioning
confidence: 99%